APLIKASI INVERTORY YANG TERINTEGRASI DENGAN INVENTARIS BARANG MENGGUNAKAN BARCODE SCANNER BERBASIS WEB - endra suseno; sherly gina supratman (FKOM UNIKU, 2021)
The process of providing tools in the Kuningan university environment is still done manually, namely by writing what items or tools are needed by each unit, the task force is submitted to the field of facilities and infrastructure managed by the University. This research was conducted to design and create and implement an integrated inventory system with inventory using barcode scanners using web network media, so that the scanner readings can be processed by the inventory application via a PC connected to a network of workstations in each task force at Kuningan University. . The development of an integrated inventory system with inventory of goods uses the RUP (Rational Unified Process) application development method. Rational Unified Processis a software engineering method developedWithusing the concept of object oriented, with activities that focus on developing models using the Unified Model Language (UML). In the inventory and inventory system, there are three actors, namely management and executor. The actor is a management who is a registered provider in the system who has full access rights to manage monitoring data and report goods data periodically. Meanwhile, two actors are not only users who have limited access rights according to their needs. In user actors, there are derivative actors who become users of the system, because those listed in the application are faculties.Keyword : web base inventory aplication